Assessment of nursing consultations for tuberculosis patients at primary health care - Déborah Raquel Carvalho de Oliveira; Bertha Cruz Enders; Caroline Evelin Nascimento Kluczynick Vieira; Larissa Soares Mariz (Universidade Federal de Goias, 2016)
The study objective was to assess nursing consultation for tuberculosis patients. A descriptive, quantitative study, conducted in a Brazilian northeast city, with 60 from primary health care nurses. A questionnaire based on the nursing consultation protocol was used with tuberculosis patients from the Health Ministry. Data collection elements were more addressed, in case of overvaluing complaints during anamnesis and physical exam (100% always investigated it) and weight measurement (96.8% conducted it). The nursing diagnosis, planning, implementation, and assessment therapeutic plan assessment were not completely conducted and, sociocultural aspects were underestimated. This fragmentation can contribute with the deficiency in operationalization of the Tuberculosis Control Plan. If scientifically and technologically amplified, Nursing Consultation can favor the development of health programs and minimize barriers permeating Tuberculosis control.